(untitled) (Research, Society and Development, 2021)
The presente work concerns the implementation of the ISO 22000:18 standard in the metal packaging field for food segments. Demonstrating that the integration of the Quality Management System (QMS/SGQ) with the Food Safety Management System (FSMS/ SGSA) can be advantageous for determining the control of hazards that have the potential to compromise the consumer health. Thus forming a system that will have as main focus to maintain the product integrity. Therefore, the aim is to demonstrate to companies of such field how they can apply ISO 22000:18 in order to develop an effective food safety system, to direct them to new study opportunities on such system analyses. Then, a bibliographical research was carried out on the subject and also a visit to a metal packaging company in the Sul Fluminense region considering the use of the PDCA cycle for such purpose. Resulting in understanding the importance of the standard through this research, establishing a new opportunity for companies to have a significant market advantage and promoting prominence with regard to safety in the food production chain.